Surface dissolution-assisted mineral flotation: A review. Issue 3 (June 2019) - Irannajad, Mehdi; Salmani Nuri, Omid; Mehdilo, Akbar
Graphical abstract: Highlights: Reviewing surface dissolution as a pretreatment in mineral flotation by investigating its mechanism and effective parameters. Surface dissolution changes the kinetic, thermodynamic and processing parameters. Effect of surface dissolution on different groups of minerals is investigated.. Surface dissolution had a significant effect on oxide and silicate minerals. Surface dissolution changes the surface, crystal and solution chemistries. Abstract: Selective flotation of minerals is a separation method based on differences in surface properties of minerals. An auxiliary pretreatment on minerals, prior to flotation, can help to increase the selectivity of separation process. Surface dissolution is a pretreatment process modifying surface properties of minerals. This critical review attempts to present the potential of the surface dissolution as a surface modification method in the mineral flotation, including parameters and mechanisms of surface dissolution, surface properties of minerals, and effect of this pretreatment on the flotation behavior of different minerals. Understanding of the different aspects of surface dissolution affecting the flotation behavior of minerals is a physicochemical challenge. The surface dissolution of minerals is led to specific changes in crystal chemistry, surface chemistry and solution chemistry of minerals that are the characteristic features in a flotation process. In addition to the mineral processing parameters, this pretreatment dissolves the mineral surface ions and affects the surface, kinetic, and thermodynamic parameters of minerals. The application potential of this method on various categories of minerals was studied. The oxide and silicate minerals had the highest potential for applying this method. In the future studies, the focus must be on the kinetic and thermodynamic characteristics of minerals, and developing of a methodology to apply the process in industrial scale.